Deteksi Kornea Mata Berbasis Segmentasi Model Warna Menggunakan Metode Template Matching - Siahaan, Ida Ulina (TIN: Terapan Informatika Nusantara, 2020)
Image processing is a system where the process is carried out with the input in the form of an image and the result is also an image. Initially, image processing was carried out to improve image quality, but with the development of the world of technology, which was marked by the increasing capacity and speed of computer processing, as well as the emergence of computational science that allowed humans to extract information from an image, image processing could not be separated by computer field. In this research, image processing is applied to detect corneas based on color model segmentation using the Template Matching Method. Template matching is a technique in digital image processing that functions to match each part of an image with the image that becomes the template (reference). The problem in detecting the cornea of ​​the eye is how to detect the cornea based on color model segmentation by matching the corneal image with the eye template image. Therefore, it is very important research that aims so that computers can have the function of detecting the cornea of ​​the eye. If computers can be designed to have intelligence closer to that of humans, of course this can facilitate human work.